The Impact of the COVID-19 Pandemic on Incidences of Atrial Fibrillation and Electrical Cardioversion at a Tertiary Care Emergency Department: An Inter- and Intra-year Analysis - Schnaubelt, Sebastian; Domanovits, Hans; Niederdoeckl, Jan; Schuetz, Nikola; Cacioppo, Filippo; Oppenauer, Julia; Spiel, Alexander O.; Laggner, Anton N. (Frontiers in Medicine, 2020)
Background: National authorities have introduced measures as lockdowns against spreading of COVID-19 and documented incidences of multiple non-COVID-19 diseases have dropped. Yet, data on workload dynamics concerning atrial fibrillation and electrical cardioversion whilst a national lockdown are scarce and may assist in future planning. Methods: Documented cases of atrial fibrillation and respective electrical cardioversion episodes at the Emergency Department of the Medical University of Vienna, Austria, from 01/01/2020 to 31/05/2020 were assessed. As reference groups, those incidences were calculated for the years 2017, 2018, and 2019. Inter- and intra-year analyses were conducted through Chi-square test and Poisson regression. Results: A total of 2,310 atrial fibrillation-, and 511 electrical cardioversion episodes were included. We found no significant incidence differences in inter-year analyses of the time periods from January to May, or of the weeks pre- and post the national lockdown due to the COVID-19 pandemic. However, the intra-year analysis of the year 2020 showed a trend toward decreased atrial fibrillation incidences (rate-ratio 0.982, CI 0.964–1.001, p = 0.060), and significantly increased electrical cardioversion incidences in the post-lockdown period (rate ratio 1.051, CI 1.008–10.96, p = 0.020). Conclusion: The decreased atrial fibrillation incidences are in line with international data. However, an increased demand of electrical cardioversions during the lockdown period was observed. A higher threshold to seek medical attention may produce a selected group with potentially more severe clinical courses. In addition, lifestyle modifications during isolation and a higher stress level may promote atrial fibrillation episodes to be refractory to other therapeutic approaches than electrical cardioversion.